2016
DOI: 10.1038/nchembio.2203
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and conformational determinants of macrocycle cell permeability

Abstract: Macrocycles are of increasing interest as chemical probes and drugs for intractable targets like protein-protein interactions, but the determinants of their cell permeability and oral absorption are poorly understood. To enable rational design of cell-permeable macrocycles, we generated an extensive data set under consistent experimental conditions for more than 200 non-peptidic, de novo-designed macrocycles from the Broad Institute's diversity-oriented screening collection. This revealed how specific function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(230 citation statements)
references
References 52 publications
8
216
0
6
Order By: Relevance
“…To ensure that the preference for 2-phenyl pyridine isn’t due to nonspecific interactions, we also looked at the 75 compounds in the initial compound library that contained the 2-phenyl pyridine moiety and confirmed that only the DOS macrolactams were hits. Substituting phenyl for 2-phenyl pyridine at R 2 increased the cLogP from 3.5 to 4.2, which in conjunction with a lowered efflux ratio, could indicate that the increased activity is due to improved cell permeability (Over et al, 2016). There were 26 compounds that contained the 2-phenyl pyridine at position R 2 and varying substituents at R 1 and all were hits to some degree in the primary screen.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the preference for 2-phenyl pyridine isn’t due to nonspecific interactions, we also looked at the 75 compounds in the initial compound library that contained the 2-phenyl pyridine moiety and confirmed that only the DOS macrolactams were hits. Substituting phenyl for 2-phenyl pyridine at R 2 increased the cLogP from 3.5 to 4.2, which in conjunction with a lowered efflux ratio, could indicate that the increased activity is due to improved cell permeability (Over et al, 2016). There were 26 compounds that contained the 2-phenyl pyridine at position R 2 and varying substituents at R 1 and all were hits to some degree in the primary screen.…”
Section: Resultsmentioning
confidence: 99%
“…48 Additional limitations for the number of rotatable bonds and polar surface area were subsequently introduced 49 . Multiple examples of orally bioavailable molecules violating rule-of-5 principles, especially including macrocycles 33, 5054 , have led researchers including Kihlberg and co-workers to develop alternative, expanded guidelines (MW ≤ 1,000 Da, # of H-bond donors below 6; # of H-bond acceptors below 15, cLogP from -2 to 10, # of rotatable bonds below 20, polar surface area below 250 Å 2 ) that are especially relevant to macrocyclic molecules such as those in our DNA-templated libraries 33, 5357 (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66] Prinzipien aus der medizinischen Chemie werden schon seit Jahrzehnten auf Peptide angewendet, einschließlich Versuchen zur Begrenzung der Molekülgrçße,der polaren Oberfläche und der Wasserstoffbrückendonoren. [64][65][66] Prinzipien aus der medizinischen Chemie werden schon seit Jahrzehnten auf Peptide angewendet, einschließlich Versuchen zur Begrenzung der Molekülgrçße,der polaren Oberfläche und der Wasserstoffbrückendonoren.…”
Section: Maskierung Von Rückgratamiden Kann Kleine Cyclischeunclassified
“…Lokey und Mitarbeiter identifizierten in diesen Studien dutzende Beispiele von cyclischen, N-methylierten Peptiden mit internen wasserstoffverbrückten Strukturen und stellten systematische Struktur-Aktivitäts-Beziehungen auf,d ie aufzeigen, welche Eigenschaften die passive Zellpenetration fçrdern. [64][65][66]137] Die Determinanten fürd ie passive Zellpenetration kleiner cyclischer Peptide sind relativ klar definiert, einige Fragen bleiben aber offen. [135] Außerdem wurde eine ungefähre untere Grenze fürd ie Hydrophobie passiv zellgängiger Moleküle bestimmt, die bei (logK hc/w ) > À2liegt, wobei K hc/w der experimentell ermittelte Kohlenwasserstoff/Wasser-Verteilungskoeffizient ist;d ie obere Grenze wird im Wesentlichen durch die Lçslichkeit bestimmt.…”
Section: Hochdurchsatzquantifizierung Hilft Die Grenzen Der Passivenunclassified